PENEGAKAN HUKUM TERHADAP PELAKU KEJAHATAN SEKSUAL TERHADAP ANAK DI INDONESIA (TINJAUAN YURIDIS TERHADAP SISTEM PIDANA DI INDONESIA) - Noor Azizah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2015)
The perpettrators of sexual crimes againts children is a crime and the very phenomenon of concern in the life of the community so that the deterrent effect of the issue againts perpetrators of pedophile became the focus of attention by all parties, in 2002 the goverment of Republic of Indonesia enacted the child protectiob law number 23 of 2002 which aim to provide protection againts indonesian children.